Anterior plagiocephaly with contralateral superior oblique overaction - Jethani Jitendra (Indian Journal of Ophthalmology, 2008)
Anterior plagiocephaly is a craniofacial anomaly related to premature unilateral synostosis. We present three cases of anterior plagiocephaly with contralateral superior oblique dysfunction. A detailed ophthalmic examination, including orthoptic assessment for the extraocular muscle misalignment, with appropriate radio-imaging was done in all the three cases. All of them showed a right-sided plagiocephaly, with overaction of the left superior oblique muscle, alternating exotropia and a dissociated vertical deviation. Two underwent surgical correction of squint. Both were well aligned after squint surgery. Plagiocephaly has been reported to simulate superior oblique muscle paresis. We report a rare occurrence of contralateral superior oblique muscle overaction in three children with anterior plagiocephaly.